2003
DOI: 10.1002/pola.10744
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuration and reversion reactions of brominated poly(isobutylene‐co‐isoprene)

Abstract: The sulfuration and reversion products of brominated poly(isobutylene-coisoprene) (BIIR) were characterized through the use of a model compound, brominated 2,2,4,8,8-pentamethyl-4-nonene (BPMN). The reaction of BPMN with S 8 produced bisallylic polysulfides of various ranks, yielding sulfur bromide intermediates that likely contributed to the rapid oxidation of allylic sulfides into thiophenes. Reductive cure reversion to pentamethylnonene was also observed in the latter stages of vulcanization. The reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Because of the presence of the active allylic bromide functionality, the bromobutyl rubbers significantly improved the rate of sulfur vulcanization and enhanced the curing compatibility with unsaturated elastomers. [13][14][15][16][17] Recently, Amit et al 18 developed a selfhealing elastomeric material based on BIIR through the chemical modification of BIIR with butyl imidazolium into an imidazolium-modified BIIR. 9 When BIIR was reacted with ZnO at high temperatures, the exomethylene isomer of the bromobutyl rubber produced the conjugated diene butyl via the dehydrobromination reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the presence of the active allylic bromide functionality, the bromobutyl rubbers significantly improved the rate of sulfur vulcanization and enhanced the curing compatibility with unsaturated elastomers. [13][14][15][16][17] Recently, Amit et al 18 developed a selfhealing elastomeric material based on BIIR through the chemical modification of BIIR with butyl imidazolium into an imidazolium-modified BIIR. 9 When BIIR was reacted with ZnO at high temperatures, the exomethylene isomer of the bromobutyl rubber produced the conjugated diene butyl via the dehydrobromination reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Over the past decade, the Whitney research group has reported various nucleophilic substitution reactions of BIIR to introduce amine, ester, ether, sulfur, ammonium, and phosphonium salt functionalities onto butyl rubbers. [13][14][15][16][17] Recently, Amit et al 18 developed a selfhealing elastomeric material based on BIIR through the chemical modification of BIIR with butyl imidazolium into an imidazolium-modified BIIR.…”
Section: Introductionmentioning
confidence: 99%
“…This elastomeric material owes its superior oxidative stability and gas impermeability to its isobutylene‐rich polymer backbone, whereas the residual unsaturation provided by isoprene isomers supports the sulfur vulcanization reactivity needed to transform IIR into thermoset articles . Cure reactivity is significantly improved by halogenating isoprene‐derived unsaturation to yield brominated poly(isobutylene‐ co ‐isoprene) (BIIR), whose allylic halide functionality is highly reactive to sulfur nucleophiles . Unfortunately, sulfur‐cure formulations require accelerators and co‐curing agents, resulting in a vulcanized product containing leachable and extractable residues.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies of the reactions of brominated poly(isobutyleneco-isoprene), or BIIR, with uncharged nucleophiles 4,5 have demonstrated the propensity of the 1-2% of allylic bromide functionality within this polymer to undergo bromide displacement under solvent-free conditions. However, analogous reactions involving alkanethiols required strong organic bases to deprotonate the substrate and render the thiolate nucleophile soluble in the elastomer phase.…”
Section: Introductionmentioning
confidence: 97%